STRATEGI PEMASARAN SALAK PONDOH (Sallacca zalacca) DI DESA PADANG PENGRAPAT KECAMATAN TANAH GROGOT KABUPATEN PASER KALIMANTAN TIMUR (Marketing Strategy of Salak Pondoh (Sallacca zalacca) in Padang Pengrapat Village Tanah Grogot Subdistrict Paser District East Kalimantan) - MUHAMMAD ABDUL AZIS JAILANI; ACHMAD ZAINI (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2018)
Marketing strategy is a comprehensive plan, integrated, and unified in the field of marketing, which is obtained from the identification of internal and external factors. The aims of this research were to identify the internal and external factors and to find the alternative of marketing strategy of salak pondoh in Padang Pengrapat Village Tanah Grogot Subdistrict Paser District. Research was held from August to October 2017. The sampling method was census with 30 respondents. Data was analyzed by using SWOT analysis. The main strength is the capital and the main opportunity is the ability to enter the market. The best alternative strategy is Strength Opportunities (SO). The strategies are maintain the quality of salak pondoh fruit to be able to retain customers and develop the market, products innovation by utilizing the existing technology, request the government assistance to increase productivity through intensification of salak pondoh field. Identification of internal factors are capital structure, land area, fruit quality, product innovation of planning type, production capacity, planning capability, human resource quality, transportation, and promotion facilities. External factors are market entry ability, technology utilization, customer, government policy, policy of environmental, economic and political, customer, competitor, product substitution, and influence of fuel price increase.